Elemental Analysis of TSP and PM10 in The Ambient Air of Aleppo City, Syria - Aziz Ramadan, Abdul; Mandil, Hasna; Hasan Ismail, Mahmoud (Asian Journal of Chemistry, 2010)
Determination of TSP and PM10 of aerodynamics particle sizes larger than 0.3 μm and heavy metals (Pb, Cd, Cu, Co, Cr, Ni, Fe, Mn and Zn) by atomic absorption spectroscopy in Aleppo city, Syria were studied. The mean TSP and PM10 levels in residential sites were at 73 to 241 and 37 to 110 μg/m3, respectively and 256 to 961 and 123 to 585 μg/m3 in industrial-residential sites, respectively. The above mentioned heavy metal concentrations were at 297 to 1112 and 201 to 734; 0.97 to 4.73 and 0.41 to 2.46; 312 to 1837 and 158 to 963; 0.14 to 1.94 and 0.08 to 0.79; 68 to 223 and 33 to 120; 0.28 to 1.87 and 0.17 to 1.22; 1116 to 4604 and 780 to 2538; 179 to 270 and 113 to 170; 370 to 1039 and 240 to 710 ng/m3 in industrial-residential sites using TSP and PM10, respectively. The results showed that, the values of TSP, PM10, Pb, Ni and Mn in industrial-residential sites atmosphere were more than the recomm-ended maximum by World Health Organization (WHO), while the value levels of all metals in residential sites were lower than the guideline values specified by WHO.